Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.7150/thno.51046
|View full text |Cite
|
Sign up to set email alerts
|

In vivo multimodal imaging of adenosine A1 receptors in neuroinflammation after experimental stroke

Abstract: Adenosine A 1 receptors (A 1 ARs) are promising imaging biomarkers and targets for the treatment of stroke. Nevertheless, the role of A 1 ARs on ischemic damage and its subsequent neuroinflammatory response has been scarcely explored so far. Methods: In this study, the expression of A 1 ARs after transient middle cerebral artery occlusion (MCAO) was evaluated by positron emission tomography (PET)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 36 publications
0
15
0
Order By: Relevance
“…Thus, available and routine clinical prediction tools of HT based on pathophysiological mechanisms are necessary to decide the best management options according to the patient's system response to stroke. In this context, experimental studies have clarified that WBC has a critical role in post-ischemic neuroinflammation and secondary neurovascular injury [15]. Within 4 to 6 h after AIS onset, circulating leukocytes adhere to the vessel wall, transmigrate through the BBB and enter the brain, subsequently releasing pro-inflammatory mediators, resulting in a secondary lesion in the penumbra surrounding the nucleus of the ischemia [8].…”
Section: Discussionmentioning
confidence: 99%
“…Thus, available and routine clinical prediction tools of HT based on pathophysiological mechanisms are necessary to decide the best management options according to the patient's system response to stroke. In this context, experimental studies have clarified that WBC has a critical role in post-ischemic neuroinflammation and secondary neurovascular injury [15]. Within 4 to 6 h after AIS onset, circulating leukocytes adhere to the vessel wall, transmigrate through the BBB and enter the brain, subsequently releasing pro-inflammatory mediators, resulting in a secondary lesion in the penumbra surrounding the nucleus of the ischemia [8].…”
Section: Discussionmentioning
confidence: 99%
“…After reperfusion for 24 h, the degree of neurological injury was performed by researchers who were blinded to the grouping ( Joya et al, 2021 ). Evaluations were performed as follows: Grade I, no nerve injury symptoms; Grade II, unable to fully extend the left front paw; Grade III, unable to fully extend the left front paw, circle to the left when walking; Grade IV, unable to fully extend the left front paw, hemiplegia to the left when walking; Grade V, loss of consciousness, unable to walk spontaneously.…”
Section: Methodsmentioning
confidence: 99%
“…After rinsing, the slices were fixed in 4% paraformaldehyde over 24 h. Image pro plus 6.0 software (Media Cybernetics, Rockville, MD, United States) was employed for infarct area analysis. Red stained areas corresponded to unaffected areas, while that stained in white was the infarcted area ( Joya et al, 2021 ). The cerebral infarct area percentage was: (cerebral infarct area/total brain area) × 100%, which is the percentage of the brain area affected by the infarct.…”
Section: Methodsmentioning
confidence: 99%
“…Focusing more on therapeutic approaches in relation with neuroinflammation, Martin et al published various papers using TSPO as reference for neuroinflammation imaging in which they examine the involvement of α4β2 nicotinic acetylcholine receptor (nAChR) [ 96 ], the cystine-glutamate antiporter system xc - [ 97 ], toll-like receptor 4 (TLR4) [ 98 ] and the adenosine A1 receptors (A1AR) [ 99 ] in the regulation of neuroinflammation after stroke. Overall, they described a very consistent time course of TSPO expression across studies and models.…”
Section: Models Of Acute Neuroinflammationmentioning
confidence: 99%
“…Altogether, these studies demonstrated that these systems are altered following stroke. More importantly, these studies also demonstrated that modulation of the α4β2 nAChR by the selective antagonist DhβE increased [ 11 C]-R-PK11195 uptake [ 96 ], whereas treatment with inhibitors of the system xc - [ 97 ] or the A1AR agonist ENBA [ 99 ] significantly decreased neuroinflammation as measured by [ 18 F]DPA-714 uptake and immunohistochemistry. In the same line, [ 11 C]-R-PK11195 PET imaging showed that neuroinflammation was reduced in TLR4 -/- mice 2 days but not 7 days post-MCAO [ 98 ].…”
Section: Models Of Acute Neuroinflammationmentioning
confidence: 99%